Swarm Control of Dynamic Objects Based on Multi-agent Technologies - Ерофеева, Виктория Александровна; Иванский, Юрий Владимирович; Кияев, Владимир Ильич (Computer Tools in Education, 2015)
In this paper we study the possibility of multi-agent systems application to the problem of swarm control. We describe the key features of swarm control and adaptive control strategy under uncertain conditions based on local voting algorithm. We also propose a consensus-based algorithm to control a swarm of dynamic objects.